Socioespatial vulnerability to droughts and floods in the Piracuruca River Sub-basin (Ceará-Piauí/Brazil) - dos Santos, Francílio de Amorim; Brito da Cruz, Maria Lúcia; Silveira Mendes, Lúcia Maria (Sociedade & Natureza, 2020)
The relevance of studies aimed at the understanding of socio-spatial vulnerability is emphasized, with the basin as a spatial cut-off, to support the prognosis and planning for droughts and floods. Thus, the objective of the research was to analyze the socio-spatial vulnerability of the Sub-basin of the Piracuruca River to the occurrence of droughts and floods. The sub-basin is located between the states of Ceará and Piauí, drains an area of 7,704 km2 and is very heterogeneous, both from a biophysical and socioeconomic point of view. The study was applied multivariate statistical model (FA) and method of estimation Principal Components Analysis (PCA), using variables - demographic, infrastructure, basic sanitation, natural, economic and social population - considering the 296 (two hundred and ninety-six) setore census, from the 2010 census. It is noteworthy that from this method / model and integration of the elements Criticity (characteristics and behavior of the population) and Support Capacity (infrastructure), it was possible to construct the Socio-Spatial Vulnerability Index Sub-basin of the Piracuruca river. Thus, the variables used to know the Criticity indicated that in 87 (29.4%) sectors of the Sub-basin predominate the upper class. In turn, it was inferred through the Capacity of Support that 137 (46.3%) sectors of the Sub-basin are in the very high class. However, the socio-spatial vulnerability index indicated the predominance of the lower class, which is distributed by 172 (58.1%) sectors of the sub-basin surveyed. However, it is necessary to invest in improving socioeconomic indicators and reducing Criticality and maintaining Support Capacity.